Spatial Characterization of Flood Intensity over the Drainage Condition of East Sempaja Village, Samarinda - Ghozali, Achmad; Rizki, Ayu Fitriana Fitriana; Mustofa, Umar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The flood events frequently impacting Samarinda City have not yet been thoroughly examined based on their intensity, particularly in the most flood-prone village in the city, East Sempaja Village. This paper employed a rigorous methodology, including K-means cluster analysis and Getis-Ord G* statistics, to reveal spatial clustering patterns based on flood intensity and residential drainage conditions in East Sempaja. The Spearman correlation was determined to identify the relationship between both factors. The present study demonstrates that using community-derived data can enhance flood disaster mitigation strategies, particularly within regions with insufficient data availability. The analysis shows that most neighborhood areas in East Sempaja have moderate to high flood intensity levels. The areas with high flood intensity are spread across the North. This paper confirms that the condition of drainage channels has a positive, yet weak, significant relationship with the level of flood intensity. Thus, optimizing drainage channels is still relevant in managing flood disasters in East Sempaja, providing practical strategies for a pressing issue.